2012
DOI: 10.1111/j.1365-2613.2012.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term experimental diabetes on adrenal gland growth and phosphoribosyl pyrophosphate formation in growth hormone‐deficient dwarf rats

Abstract: The availability of growth hormone (GH)-deficient dwarf rats with otherwise normal pituitary function provides a powerful tool to examine the relative role of hyperglycaemia and the reordering of hormonal factors in the hypertrophy-hyperfunction of the adrenal gland that is seen in experimental diabetes. Here, we examine the effects of long-term (6 months) experimental diabetes on the growth of the adrenal glands; their content of phosphoribosyl pyrophosphate (PRPP); and the activity of the PRPP synthetase, G6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The same study showed that reestablishment of GH levels using viral-mediated gene transfer in the dorsal hippocampus could abolish the stress-related effects on behavior in those rats [40]. Interestingly, in GH-deficient rats, GH prevents adrenal weight growth, which is normally seen in early experimental diabetes [41]. Along similar lines, insulin-like growth factor, the downstream effector of GH, increases adrenal growth [42].…”
Section: Discussionmentioning
confidence: 86%
“…The same study showed that reestablishment of GH levels using viral-mediated gene transfer in the dorsal hippocampus could abolish the stress-related effects on behavior in those rats [40]. Interestingly, in GH-deficient rats, GH prevents adrenal weight growth, which is normally seen in early experimental diabetes [41]. Along similar lines, insulin-like growth factor, the downstream effector of GH, increases adrenal growth [42].…”
Section: Discussionmentioning
confidence: 86%
“…Comparative analysis regarding the development of several types of diabetes in both humans and animals (Long et al 2004;Rao et al 2011) is imperative. Experimental models on mild diabetes are still controversial regarding dose, period of administration and route of drug induction, as well as age and species of animal model (Cuman et al 2001;Arora et al 2009;Kunjara et al 2012;Sinzato et al 2012;Damasceno et al 2013). Recently, mild diabetes model was characterized by changes in two or more points in the glucose curve during OGTT (Santos et al 2015).…”
Section: Discussionmentioning
confidence: 99%